The encyclopedia of volcanoes - Sigurdsson, Haraldur (Academic Press, 2015)
Volcanoes are unquestionably one of the most spectacular and awe-inspiring features of the physical world. Our paradoxical fascination with them stems from their majestic beauty and powerful, sometimes deadly, destructiveness. Notwithstanding the tremendous advances in volcanology since ancient times, some of the mystery surrounding volcanic eruptions remains today. The Encyclopedia of Volcanoes summarizes our present knowledge of volcanoes; it provides a comprehensive source of information on the causes of volcanic eruptions and both the destructive and beneficial effects. The early chapters.